2006
DOI: 10.1007/s10327-005-0254-8
|View full text |Cite
|
Sign up to set email alerts
|

Damping-off of cabbage plug seedlings caused by Pythium ultimum var. ultimum in Japan

Abstract: In October 2004, Pythium ultimum var. ultimum was isolated from rotten stems of cabbage plug seedlings in a commercial nursery in Mie Prefecture (Japan). The isolated fungus was then used to inoculate seedlings and subsequently reisolated from the seedlings with the damping-off disease, showing that P. ultimum var. ultimum is a new pathogen causing cabbage seedling disease.Key words Cabbage · Damping-off · Plug seedlings · Pythium ultimum var. ultimumIn October 2004, several plug seedlings of cabbage (Brassica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…The pathogenic infection causes the pre-emergence mortality of seedlings. Various phytopathogens, including Rhizoctonia solani [ 2 , 3 , 4 ], Pythium ultimum [ 5 ], Pythium aphanidermatum [ 6 ], and Fusarium moniliforme [ 7 ] have been reported to cause damping-off in cabbage. Synthetic chemical fungicides are routinely used to control the damping-off disease of vegetable crops [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic infection causes the pre-emergence mortality of seedlings. Various phytopathogens, including Rhizoctonia solani [ 2 , 3 , 4 ], Pythium ultimum [ 5 ], Pythium aphanidermatum [ 6 ], and Fusarium moniliforme [ 7 ] have been reported to cause damping-off in cabbage. Synthetic chemical fungicides are routinely used to control the damping-off disease of vegetable crops [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…capitata ) is one of the most popular leafy vegetables and plug systems are widely used for its seedling production ( 21 , 39 ). Recent studies reported that many diseases affect cabbage plug seedlings in large commercial nurseries in Japan ( 17 19 , 22 ). The incidence of damping-off, caused by Alternaria brassicicola (Schweinitz) Wiltshire, is the highest during the growing season ( 17 , 18 , 23 , 25 ).…”
mentioning
confidence: 99%
“…キャベツ(Brassica oleracea L.)は国内外を問わず,葉物野Pythium ultimum Trow var. ultimum および P. aphanidermatum (Edson) Fitzpatrick によるピシウム腐敗病(Kubota et al, 2006; 森,1996)と P. megalacanthum de Bary および P. zingiberis 群馬県農業技術センター(〒 379-2224 群馬県伊勢崎市西小保方町 493) Gunma Agricultural Technology Center, 493 Nishi-Obokata,…”
unclassified